A Brief Overview on Facile Synthesis and Challenging Properties of Graphene Nanocomposite: State-of-the-art - Kumar Behera, Tapan; Pradhan, Snehalata; Behera, Priyanka; Kumar Satapathy, Pramod; Mohapatra, Priyabrata (Asian Journal of Chemistry, 2022)
This review work aims to present a brief study on the unique carbon allotrope graphene and its composite with nanoparticles. Graphene plays an important role in physics, chemistry, biotechnology, medical science, materials science and many more fields. The wide applications of graphene are based on its unique structure, exceptional physical properties, chemical tunability and dramatically electronic arrangement. The current world demands the energy conversion, digital technology and medical diagnoses in lower potential value, low cost, high reproducibility and high portability. Graphene nanocomposite possessing the above criteria and able to fulfill the worlds demand and become the most rising shining star in the horizon of material science research field. This review elaborates about historical background, structural feature, developed synthesis process, unique properties, characterizations and its different magnificent biosensor applications. In particular, the general overview study of its different fascinating properties such as mechanical, optical, magnetic, quantum hall effect, electronic transport properties and these makes graphene nanocomposite a rising tool for different biosensor applications.